Hygienic evaluation of heavy metals levels in meat tissues and fats after adding selenium and zinc (Journal of Pharmaceutical Negative Results, 2022)
Given the great diversity of heavy metals in the environment and their concentration within different feds, it is impossible to achieve levels of contamination below the detection limit for all elements in tissues. Therefore, it is necessary to work at different levels in order to control contamination with heavy metals and reduce the risks of human exposure in the fed chain, as well as prepare detection methods to control these pollutants in the fed chain and different body tissues from heavy metals. Heavy metals were analyzed in meat and fat of lambs of Kurdi sheep after taking a dose of selenium at a concentration of 0.5 mg / kg and zinc at a concentration of 100 mg / kg for a period of 90 days separately or their combination. The results showed the determination of the metallic elements of each of Selenium (Se), zinc (Zn), Copper (Cu), Iron (Fe), Palladium (Pd), thallium (Ti), Antimony (Sb), Tin (Sn), Molybdenum (Mo), Tungsten (W), Strontium (Sr), Tantalum (Ta), argon (Ar), Lead (Pb), Nickel (Ni), Platinum (Pt), Bromine (Br), arsenic (As), Zirconium (Zr), Bismuth (Bi), Cobalt (Co) and Iridium (Ir) in meat and fat tissues, there was no percentage of mineral elements for each of Silver (Ag), Cadmium (Cd), Manganese (Mn), indium (In), mercury (Hg), Platinum (Pt), Vanadium (V), Rhenium (Re) and Chromium (Cr) Concentrations of some metal elements were within the permissible limits It was approved by WHO, ANZFA, and Institute of Medicine, but some mineral elements do not have data on permissible limits.It is concluded from these results that supplementation of selenium and zinc improves animal health and does not have a harmful effect on meat and fat tissues. It needs careful studies to know the toxic concentration of the metallic elements that were challenged for the first time.